NETWORK AS A HYPERTEXTUALITY SPACE IN THE CONTEXT OF CULTURE IN THE INFORMATION ERA - Іщук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the phenomenon of virtual hypertextuality. A typologization of hypertexts in the Internet is attempted.